2021
DOI: 10.37201/req/051.2021
|View full text |Cite
|
Sign up to set email alerts
|

Map of sexually transmitted disease care in Spanish emergency departments

Abstract: Objective. To determine the approaches used in Spanish emergency departments (EDs) in patients suspected of having sexually transmitted diseases (STD) analysed according to the size of the hospital, ED census and autonomous community. Material and methods. Questionnaire to the heads of 282 public EDs (7/24) related to emergency routines for patients with suspected STD. Results compared using odds-ratio (OR) and 95% confidence interval (95%CI) according to hospital size (large vs medium-small: ≥500 vs. <500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…U.S. studies show that 1.3/1,000 of the diagnoses recorded in emergency care are for an STI [ 57 ]. A recent Spanish study conducted in 250 hospital emergency departments (ED), with a population coverage of around 45.7 million people and 19.4 million attendances, showed that approximately 71,000 of those attendances corresponded to a suspected STI, which means an incidence of 3.7/1,000 in our country [ 58 ]. A noteworthy aspect of this study is that only 36.4% of Spanish hospital EDs have a therapeutic approach protocol for STI, which is more frequent in large hospitals and in hospital EDs with a high influx of patients [ 58 ].…”
Section: What Is the Burden Of Sti In The Emergency Department?mentioning
confidence: 99%
See 2 more Smart Citations
“…U.S. studies show that 1.3/1,000 of the diagnoses recorded in emergency care are for an STI [ 57 ]. A recent Spanish study conducted in 250 hospital emergency departments (ED), with a population coverage of around 45.7 million people and 19.4 million attendances, showed that approximately 71,000 of those attendances corresponded to a suspected STI, which means an incidence of 3.7/1,000 in our country [ 58 ]. A noteworthy aspect of this study is that only 36.4% of Spanish hospital EDs have a therapeutic approach protocol for STI, which is more frequent in large hospitals and in hospital EDs with a high influx of patients [ 58 ].…”
Section: What Is the Burden Of Sti In The Emergency Department?mentioning
confidence: 99%
“…A recent Spanish study conducted in 250 hospital emergency departments (ED), with a population coverage of around 45.7 million people and 19.4 million attendances, showed that approximately 71,000 of those attendances corresponded to a suspected STI, which means an incidence of 3.7/1,000 in our country [ 58 ]. A noteworthy aspect of this study is that only 36.4% of Spanish hospital EDs have a therapeutic approach protocol for STI, which is more frequent in large hospitals and in hospital EDs with a high influx of patients [ 58 ]. The protocolization of STI in the ED is important for 5 reasons: 1) clinical protocols improve the quality of care; 2) STI are a public health problem so their proper management has implications not only for the patient; 3) sample collection, transport and processing are especially important in some frequent STI such as gonococcal infection, as Neisseria gonorrhoeae is very sensitive to environmental conditions; 4) the successive emergence of antibiotic resistance to gonococcus has forced frequent modifications of empirical treatment guidelines for STI worldwide [ 59 ]; and 5) ensuring subsequent follow-up is important in order to ensure clinical cure, screen for other STI, interrupt the chain of transmission and implement preventive and sexual health promotion measures.…”
Section: What Is the Burden Of Sti In The Emergency Department?mentioning
confidence: 99%
See 1 more Smart Citation